Comparison of two atrophic rhinitis vaccines for young pigs - D A Schoneweis; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1990)
Two farrowing groups (340 pigs) were used to evaluate two atrophic rhinitis vaccines (Atrobac III and Tocivac for the young pig. Both vaccines were effective, because no clinical evidence of atrophic rhinitis was observed for either treatment during the experiment. Although the swine herd had been observed in previous farrowing do have various degrees of conjunctivitis, none was observed in the pigs vaccinated with either vaccine. Weight gains of pigs at 14 d and 35 d postweaning were the same for each treatment.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Starter; Performance; Disease; Rhinitis